Confirmatory factor analysis of employee trust scale - Chua, Bee Seok; Getrude Cosmas; Jasmine Adela Mutang; Shazia Iqbal Hashmi (Institute of Research Advances, 2016)
A The Employee Trust Scale is developed for a study that examines employees’ trust towards their supervisors. This 49-item measure is a newly created scale by the researchers based on the findings of their previous study “Exploring the Concept of Trust in Malaysia Society”. Through the result of exploratory factor analysis, Chua et al. (2015) was able to extract three factors, labeled ‘trustworthiness, ‘position status’and ‘relationship’ which accounted for 62.49% of the total variance and the scale provided reliable assessment. Considering the existing assumptions of three dimensions of employee trust toward their supervisor as established by Chua et al. (2015), in this paper, a confirmatory factor analysis was conducted to test the dimensionality of the Employee Trust Scale. This analysis was conducted with Structural Equation Modelling which was used to assess the fit of the model. In addition, reliability and validity of the model was measured. A total of 514 (274 males and 228 females) employees who were selected randomly from public and private organization sectors in Kota Kinabalu, Sabah, Malaysia were involved in this study. Their ages ranged from 21 to 59 years old with an average of 34.34 years old and their average tenure with their current organization was 8.46 years (with s.d. = 8.11 years). Finding of the present research can help in enhancing productivity within an organization by improving trust and relationship building between employees and employer.